Analisis Keterampilan Membaca Peserta Didik Dengan Menggunakan Metode Eja Berdasarkan Jurnal Cendekia Pada Pembelajaran Tematik Kelas II SDN 07 Sikabu - Wahyuni, Sisri; Agustina, Dila (Jurnal Riset Pendidikan Dasar Dan Karakter, 2023)
This research is motivated by the low reading skills of students in thematic learning and to make it easier for students to read, educators must be able to choose the right method to improve students' reading skills. The Spell method is a learning method that emphasizes letter-by-letter recognition. The purpose of this study was to examine students' reading skills using the spelling method, especially in the journals of the last 5 years. The research method used in this research is library research. The author collects more than 10 references related to history, reading skills using the spelling method. Data collection techniques used through library research. The results of this study were obtained in journals published in the last 5 years. The spelling method has a significant effect on the achievement of cognitive competence and problem solving skills. Based on the results of reviews from these journals, the spelling method can be categorized as very suitable to be applied to learning in elementary schools. Based on the results of the study, the use of the spelling method in learning in elementary schools was stated to be very good